2009
DOI: 10.1063/1.3224175
|View full text |Cite
|
Sign up to set email alerts
|

Efficient organometallic spin filter based on Europium-cyclooctatetraene wire

Abstract: Electronic structures, magnetic, and transport properties of organometallic sandwich molecular wire (SMW) constructed with altering europium (Eu) atoms and cyclooctatetraene (COT) rings have been studied by spin-polarized first-principles calculations and nonequilibrium Green’s function method. The one-dimensional Eu-COT SMW is predicted to be a ferromagnetic semiconductor. The calculated average magnetic moment per Eu atom is about 7μB. The total magnetic moment (TMM) of Eun(COT)n+1(n=1–4) sandwich clusters i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 41 publications
1
54
1
Order By: Relevance
“…8 These clusters exhibit unusual magnetic properties. For example, the magnetic moment of V n Bz n+1 increases linearly along with the size; 13 Eu n COT n+1 possess extraordinarily high magnetic moments and high spin filter efficiency; 14,23 hybrid TM n (FeCp 2 ) n+1 clusters show significant magnetic moment enhancement as compared to their constituted monometallic counterparts. 15,21,24 In addition, many infinite 1D sandwich molecular wires exhibit exceptional high spin filter efficiency, which are important in the application of spintronics.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…8 These clusters exhibit unusual magnetic properties. For example, the magnetic moment of V n Bz n+1 increases linearly along with the size; 13 Eu n COT n+1 possess extraordinarily high magnetic moments and high spin filter efficiency; 14,23 hybrid TM n (FeCp 2 ) n+1 clusters show significant magnetic moment enhancement as compared to their constituted monometallic counterparts. 15,21,24 In addition, many infinite 1D sandwich molecular wires exhibit exceptional high spin filter efficiency, which are important in the application of spintronics.…”
Section: Introductionmentioning
confidence: 97%
“…15,21,24 In addition, many infinite 1D sandwich molecular wires exhibit exceptional high spin filter efficiency, which are important in the application of spintronics. 11,23,25 However, previous studies mostly focused on mononuclear metal center sandwich clusters. Planar aromatic ligands can accommodate two or more TMs to form stable multinuclear metal center sandwich structures, and a few efforts have been dedicated to this field both experimentally [26][27][28][29][30] and theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al pointed out that the clusters Eu-COT and Fe-COT are nearly perfect spin filters which are sandwiched between two Au(100) surfaces from the spin transport calculations. 20,21 In order to understand the physics and mechanism of the sandwich complexes, we study the stability of the structure, a) Author to whom correspondence should be addressed. the electronic and magnetic properties of the molecular wires (Mt-COT) (Mt = Sc-Zn, COT = C 8 H 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18][19] One of the novel methods to design molecular magnets provided by Weng et al is to replace edge benzene rings by cyclopentadienyl in transition metal multidecker sandwich complexes. [8][9][10][11][12][13][14][15][16][17][18][19] One of the novel methods to design molecular magnets provided by Weng et al is to replace edge benzene rings by cyclopentadienyl in transition metal multidecker sandwich complexes.…”
Section: Introductionmentioning
confidence: 99%
“…For systems like V n Bz n+1 , experimental studies have shown that the spin multiplicity increases linearly with the cluster size, which is very important to make a wire which transmits spin signals over long distances so that spin manipulation is possible. [14][15][16][17]24 However, there are still demand for more realistic systems which show efficient spin polarized transport. Cp 2 BzV 2 infinite molecular wires 24 have been theoretically studied along with V 2n+1 Cp 2n+2 , V n (FeCp 2 ) n+1 , and V 2n Ant n+1 (Ant = anthracene), but electronic structure and transport properties of Cp 2 BzV 2 need a deeper understanding in order to tailor them.…”
Section: Introductionmentioning
confidence: 99%